Community Acquired Lower Urinary Tract Infections in Primary Care: Causative Agents and Antimicrobial Susceptibility - Arman, Dilek; Agalar, Canan; Dizbay, Murat; Tunccan, Ozlem Guzel; Keten, Derya Tozlu; Aygun, Gokhan; Alpay, Yesim (Galenos Yayincilik, 2012)
Introduction: The aim of this study was to determine the causative agents of community-acquired lower urinary tract infections (CALUTIs) in primary care. We also aimed to evaluate the antimicrobial susceptibility rates of urinary Escherichia coli isolates to various oral antibiotics and to assist primary care physicians with antibiotic selection. Materials and Methods: The study was performed in 55 primary care centers in 13 cities between May and July 2009. Adult patients with at least two of dysuria, pollakiuria, nocturia, suprapubic tenderness, or blurred urine symptoms, but not fever, were included in the study. Urinary samples were obtained and patient data were recorded at the primary care centers. Results: Totally, 400 patients were enrolled. In 175 (43.8%) patients, urine cultures yielded a urinary pathogen. The most frequently encountered pathogen was E. coli (62.8%). Among E. coli isolates, the lowest resistance rates were detected for nitrofurantoin (0.9%) and fosfomycin (3.6%) and the highest for trimethoprim/sulfamethoxazole (43.6%) and amoxicillin/clavulanate (41%). Resistance rates to quinolones were 23.6% for ciprofloxacin and 21% for levofloxacin. Minimum inhibitory concentration (MIC)(50) and MIC90 values for ciprofloxacin and levofloxacin were 0.015 and 32 mu g/mL and 0.06 and 16 mu g/mL, respectively. Quinolone resistance was significantly higher in patients who received an antimicrobial treatment within the last three months (p< 0.001). Extended spectrum beta-lactamase (ESBL) positivity was detected in 15 of 110 (13.6%) E. coli isolates. Quinolone resistance was significantly higher among ESBL positive than ESBL negative strains (53.3% vs. 15.8%, p= 0.002). Conclusion: In conclusion, the most frequent causative agent in CALUTIs was E. coli. The lowest resistance rates among E. coli isolates were detected for nitrofurantoin and fosfomycin. Resistance rates to quinolones were over 20% in our study. Our study provides important data about the causative agents and their antibiotic susceptibilities and also contains valuable data for rational antibiotic usage in the treatment of CALUTI in Turkey.
Keywords: Urinary tract infections; Escherichia coli; community-acquired infections; antimicrobial drug resistance